2016
DOI: 10.1097/rlu.0000000000001277
|View full text |Cite
|
Sign up to set email alerts
|

Uterine Cervical Metastasis From Primary Rectal Adenocarcinoma on PET/CT and MRI

Abstract: FDG avid uterine cervical masses are most commonly due to primary cervical carcinoma; however, history and differential diagnoses are critical when interpreting FDG PET/CT studies. A 51-year-old woman with newly diagnosed moderately differentiated adenocarcinoma of the rectum underwent FDG PET/CT for staging, which revealed the hypermetabolic primary rectal tumor and nodal metastases. Additionally, FDG avid focus in the anterior cervix without a CT correlate was present. Cervical metastasis was suspected, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The final pathology supported a diagnosis of metastasis from rectal carcinoma. Rare distant metastasis sites of colorectal cancer include tonsil, 1 kidney, 2 vagina, 3,4 uterus, 5,6 thigh muscle, 7 and thyroid 8 . However, solitary abdominal wall metastasis from rectal adenocarcinoma is very rare.…”
mentioning
confidence: 99%
“…The final pathology supported a diagnosis of metastasis from rectal carcinoma. Rare distant metastasis sites of colorectal cancer include tonsil, 1 kidney, 2 vagina, 3,4 uterus, 5,6 thigh muscle, 7 and thyroid 8 . However, solitary abdominal wall metastasis from rectal adenocarcinoma is very rare.…”
mentioning
confidence: 99%
“…It is reported that FDG PET/CT was helpful in detecting local recurrence, especially extraluminal recurrence of rectal cancer 1–3 . Several cases have reported PET/CT findings of rare metastatic/recurrent pelvic sites from rectal cancer including vagina, 4 uterine, 5,6 and penile, 7 which were hypermetabolic masses with SUVmax ranging from 7.4 to 11. In addition to malignant metastases, active inflammation may also result in high glucose metabolism 8 .…”
mentioning
confidence: 99%